The Semiotic Representation of Gay Identity in Pixar’s Out (2020) (Sastra Inggris UNPAM, 2025)
This study aims to examine the representation of gay identity in the animated short movie Out (2020) by applying Peirce’s (1932) semiotic theory and Cass’s theory (1979). A qualitative descriptive method is used to interpret verbal and non-verbal signs related to sexual identity. The data are taken from twenty scenes containing relevant signs. Each sign is analyzed using Peirce’s triadic model, which consists of the representamen, the object, and the interpretant to explain how meaning is formed in the movie and later connected to Cass’s theory of gay identity stages. The findings showed that gay identity in Out (2020) was expressed through visual and verbal elements such as gestures, expressions, and dialogues that reflected Greg’s internal struggle and his developing self-acceptance. Greg was found to experience five stages of Cass’s identity formation model: confusion, tolerance, acceptance, pride, and synthesis. In summary, this study revealed that animated movie can effectively present topics related to sexual identity. It also highlights how signs in a movie can help explain personal experiences, family dynamics, and the emotional journey of LGBTQ+ characters.